Neuron-glia interaction at the receptor level affects olfactory perception in adult Drosophila - Laura Calvin-Cejudo; Fernando Martin; Luis R. Mendez; Ruth Coya; Ana Castañeda-Sampedro; Carolina Gomez-Diaz; Esther Alcorta (iScience, 2023)
Summary: Some types of glia play an active role in neuronal signaling by modifying their activity although little is known about their role in sensory information signaling at the receptor level. In this research, we report a functional role for the glia that surround the soma of the olfactory receptor neurons (OSNs) in adult Drosophila. Specific genetic modifications have been targeted to this cell type to obtain live individuals who are tested for olfactory preference and display changes both increasing and reducing sensitivity. A closer look at the antenna by Ca2+ imaging shows that odor activates the OSNs, which subsequently produce an opposite and smaller effect in the glia that partially counterbalances neuronal activation. Therefore, these glia may play a dual role in preventing excessive activation of the OSNs at high odorant concentrations and tuning the chemosensory window for the individual according to the network structure in the receptor organ.